2014
DOI: 10.4161/mabs.27876
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemical modifications of sites in the CDRs of recombinant antibodies

Abstract: Modifications like asparagine deamidation, aspartate isomerization, methionine oxidation, and lysine glycation are typical degradations for recombinant antibodies. For the identification and functional evaluation of antibody critical quality attributes (CQAs) derived from chemical modifications in the complementary-determining regions (CDRs) and the conserved regions, an approach employing specific stress conditions, elevated temperatures, pH, oxidizing agents, and forced glycation with glucose incubation, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
161
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 52 publications
5
161
0
Order By: Relevance
“…The Asn384/389 deamidation rate ranged from 70 ~ 144 x 10 −3 day −1 , which was the highest among all Asn sites. 1 The R square values for all three mAbs were >0.99.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The Asn384/389 deamidation rate ranged from 70 ~ 144 x 10 −3 day −1 , which was the highest among all Asn sites. 1 The R square values for all three mAbs were >0.99.…”
Section: Resultsmentioning
confidence: 86%
“…Deamidation of several Asn residues in the complementary-determining regions (CDRs) of IgG mAbs have been reported to affect antigen binding. 1–4 Recent studies have also shown that changes in the charge distribution on the protein surface could alter mAb pharmacokinetics (PK) by affecting FcRn-IgG dissociation. 5,6 Thus, the potential risk of deamidation at each site needs to be evaluated to ensure product stability.…”
Section: Introductionmentioning
confidence: 99%
“…Carboxyl-terminal lysine processing, deamidation, oxidation, isomerization, mutation, and changes in glycosylation are examples of modifications that can be extremely small in size (Dalton range), but can have a substantial effect on how the antibody functions. 3 To fully characterize the nature and effects of post-translational modifications, a comprehensive analytical approach combining bioanalytical and structural studies should be considered. Analytical chromatography methods such as ion exchange and hydrophobic interaction chromatography (HIC) are effective analytical tools for uncovering changes in antibody charge variance or changes in hydrophobicity that can accompany post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%
“…After administration, the accumulated succinimide hydrolyzes to Asp and/or isoAsp under the physiologic pH. In mAbs, deamidation has been reported in the Fc regions [4,5] and the CDRs [6][7][8][9][10][11][12]. Deamidation in the CDR regions could affect drug efficacy [10,12].…”
Section: In Vivo Mab Modificationsmentioning
confidence: 99%
“…In mAbs, deamidation has been reported in the Fc regions [4,5] and the CDRs [6][7][8][9][10][11][12]. Deamidation in the CDR regions could affect drug efficacy [10,12]. Deamidation can accumulate more rapidly in in vitro and in vivo serum samples than that in PBS or formulation buffers [7,13,14], which raises concerns about loss of potency and the potential immunogenicity of the therapeutics after administration.…”
Section: In Vivo Mab Modificationsmentioning
confidence: 99%